OBSERVATIONS ON SOME ASPECTS OF BIOLOGY OF SILVERBELLY LEIOGNATHUS BINDUS (VALENCIENNES) FROM KAKINADA - Murty, V Sriramachandra (Indian Journal of Fisheries, 2011)
The length-weight relationship of Leiognathus bindus can be described bythe equation log W = —4.77709 + 2.96182 log L. The length at first maturity isestimated as 80 mm. This species is a fractional spawner and appears to releasethe ova in at least two spawning acts during the course of one year; it appears tospawn in almost all months, with a peak during December-February. Based on lengthfrequencydistribution, the species attain 65 and 90 nrni at the completion offirst and second year respectively.